PERAN NON PERFORMING FINANCING (NPF) DALAM HUBUNGAN ANTARA DEWAN KOMISARIS INDEPENDEN DAN PROFITABILITAS BANK SYARIAH - Rahman, Taufikur; Safitrie, Dian (Universitas Islam Negeri Sunan Kudus, 2018)
This study empirically examined the role of Non Performing Financing (NPF) as the intervening variable on the relationship between independent board and profitability. The population used in this study is all Islamic banking of Indonesia that consist of 13 Islamic banking. The writer took 11 Islamic banking as the sample of this research. The sampling technique used in this research is purposive sampling technique.Types of data used are secondary data. The data of this study collected from Islamic Banking companies that issue an annual report and a report on the implementation of good corporate governance periode of 2011-2015. This study has utilized path analysis to analyze the mediating effect of NPF on the relationship between board size independence and profitability. The result of this study suggest that empirically NPF does not mediate the relationship between independent board and profitability, so empirically NPF can not play the role as the intervening variable.The result of this study also suggest that independent board has positif effect on profitability (ROE), independent board has negative effect on NPF and NPF has not effect on profitability (ROA).